DISTINGSI DIGITAL BRANDING TSAMARA AMANY SEBAGAI CALON ANGGOTA LEGISLATIF PEREMPUAN MILENIAL DI INSTAGRAM - Yanuar Budi Haristono (Metacommunication: Journal of Communication Studies, 2021)
Women's representation in the Indonesian legislative still does not meet the expectations of 30% of the total. In addition to the lack of representation of women in the legislature, the representation of young people especially the millennial generation is very minimal in the ranks of DPR members in the 2014-2019 period. Tsamara Amany Alatas, a 22-year-old woman who graduated from Communication Studies at Paramadina University, went on to run as a legislative candidate. Tsamara built his distinction on social media, especially Instagram. Tsamara always showed the feminine and young side he had as his campaign strategy. The research method used in this study is qualitative research using content analysis of Instagram posts which are then supported by interview data to informants. The results of the study indicate that the distinctive formation built by Tsamara where change appeared when he had entered the world of politics with an appearance that reflected young people who were casual and friendly with the aim of forming the perception that Tsamara wanted to be closer and accepted by society, so that he was not distant from society so that the branding of the millennial politicians that he brings can be conveyed well.